Do Grants to Communities Lead to Better Health and Education? - World Bank (Washington, DC, 2014)
Indonesia, like many middle income countries, has difficulty providing universal access to education and adequate access to healthcare, particularly in poor and rural areas. To tackle these problems, the Government of Indonesia launched two large-scale programs in 2007. The programs both relied on cash transfers, but one targeted households and one targeted communities. In both cases, the transfers were designed to encourage families to meet basic health and education indicators, including prenatal visits for pregnant women, childhood immunization, regular weight monitoring, and school attendance. To push communities to focus on the most effective policies, a portion of subsequent year grants is based on how well communities do in meeting the previous year's health and education targets. In this way, the program takes aspects of conditional cash transfer and pay-for-performance programs and reformulates them to encourage community-wide performance and accountability. In order to test the effectiveness of linking grants to the previous year's performance, a second version of the program was carried out in which communities received the money irrespective of the previous year's performance. The grants have ranged from an average of $8,500 in 2007 to $18,200 in 2009. This World Bank supported program now reaches about 5.4 million people.